Algoritmo de Encriptación para Imágenes a color basado en Sistemas Caóticos - Amaya Barrera, Isabel; Suárez Parra, César Augusto; Santos Bustos, Daniel (Ingeniería, 2020)
Context: Taking advantage of the foundations of the theory of non-linear dynamic systems, we propose an encryption model for color images based on chaotic systems, which satisfies security standards in accordance with the challenges faced by society. Method: A symmetrical algorithm is proposed using Arnold's chaotic Cat system for permutation and for diffusion Chen's hyperchaotic system or Lorenz's hyperchaotic system, a parallel programming in implementation is used to reduce execution times. Results:Performance metrics are applied to evaluate the security of the proposed cryptographic model, finding that the indicators obtained are framed within those published in recent articles that address the problem of security through chaos. Conclusions: The results obtained confirm that the use of chaos theory as a tool for strengthening security schemes in communications is a good alternative, particularly when referring to image transfer.